The labor right to digital disconnection in the dependency relationship with the employer - Zambrano Barre, Liz Stefany (2025)
The labor disconnection is a right that entitles the worker to disconnect from any electronic device and avoids communication or work orders outside working hours. The objective of the study was to examine the labor right to digital disconnection in the relationship of dependence with the employer in Ecuador. The approach is qualitative, descriptive. The design is documentary. The information was collected through a bibliographic review, using scientific and academic databases, such as: Dialnet, Google Academic, Scielo, Scopus, Redalyc, among others. The results reveal that there is a violation of the labor right to digital disconnection, although there is a legal framework, there is no specific legal regulation for its application. It is concluded that, in Ecuador there is a norm that regulates digital disconnection, however, there is a lack of structure in its procedure and application, therefore, this right has been violated